2020
DOI: 10.1016/j.jadohealth.2019.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Who is JUULing and Why? An Examination of Young Adult Electronic Nicotine Delivery Systems Users

Abstract: Purpose: The purpose of this study was to compare characteristics of usual JUUL users versus other electronic nicotine delivery systems (ENDS) users, examine differences in reasons for use and perceptions across ENDS user groups, and identify significant correlates of usual JUUL use. Methods: This study used data from 510 young adult ENDS users (ages 18e29 years) from Wave 7 (Spring 2018) of the Marketing and Promotions Across Colleges in Texas Project (Project M-PACT). Chi-Square analyses, independent t-tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 32 publications
2
39
0
1
Order By: Relevance
“…The nicotine message, although written to highlight effects other than addiction, elicited more muted message reactions. As "nicotine hit" is increasingly a motivator of youth Juul use [35], conveying the negative effects of nicotine exposure may not resonate with teens. Messages about burns from e-cigarettes exploding and the product designs of e-cigarettes were consistently rated the lowest for intended message reactions; this may be a result of low perceived likelihood of explosions because of underreporting [36] and the difficulty in countering established attitudes from the successful marketing of a sleek product [25].…”
Section: Discussionmentioning
confidence: 99%
“…The nicotine message, although written to highlight effects other than addiction, elicited more muted message reactions. As "nicotine hit" is increasingly a motivator of youth Juul use [35], conveying the negative effects of nicotine exposure may not resonate with teens. Messages about burns from e-cigarettes exploding and the product designs of e-cigarettes were consistently rated the lowest for intended message reactions; this may be a result of low perceived likelihood of explosions because of underreporting [36] and the difficulty in countering established attitudes from the successful marketing of a sleek product [25].…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the first studies to report on long-term health consequences from using e-cigarettes. Linked with frequent use and addiction of Juuls, the study by Case et al [27] reported that Juul, the most popular pod-based e-cigarette, has a high nicotine concentration, and most adolescents reportedly use it to obtain a higher nicotine hit. The authors further expressed concern that Juul users go on to use cigarettes for want of an even higher nicotine hit, leading to dual use.…”
Section: Editorialmentioning
confidence: 99%
“…Yet another study showed that adolescents across the board See Related Articles on pp. 18,27,34,39,48,56 www.jahonline.org are using e-cigarettes, and that "emotionally healthier" adolescents are more attracted to e-cigarettes compared with combustible cigarettes [34]. There is a need for a future systematic review to synthesize evidence on the link between mental health and adolescent e-cigarette use and to assess reasons for these contradictory findings, which are potentially related to differences in products, measures used, and when the studies were conducted.…”
Section: Editorialmentioning
confidence: 99%
“…Additional research has documented the emergence of JUUL-compatible pods, some containing nicotine concentrations as high as 6.5% [ 13 ]. With approximately 90% of adult daily ever smokers beginning before 18 years of age [ 19 ] and a lack of public understanding regarding JUUL’s highly concentrated nicotine levels [ 20 ], it has been hypothesized that JUUL poses a risk to younger populations for developing nicotine dependency [ 21 , 22 ]. Consequently, nicotine dependency developed in adolescence may result in addiction and potentially a later transition to traditional combustible cigarettes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%